SENSORIAL CUES CHANGES AND THE AUTOMATIZATION OF A CATEGORIAL SEARCH TASK COMPONENTS - García Sevilla, Julia; Romero Medina, Agustín (Anales de Psicología / Annals of Psychology)
After confirming (García-Sevilla y Romero, 1991) the facilitation of sensorial cues in automatizing that some components of a categorial search task, now in this experiment the interfering role of inversion technique (change of target stimulus after the sensorial cue) along training is analyzed. The results (with a sample of 60 adults subjects) shows a negative transfer effect at the training start, especially with total incompatibility between sensorial cue and stimulus target. The presence of sensorial cues reduce the amount of resources asigned to categorial search task, producing so a partal automatization of some of this components.